EUS-guided placement of fiducial markers for stereotactic body radiation therapy in pancreatic cancer: feasibility, security and a new quality score - Figueiredo, Mariana; Bouchart, Christelle; Moretti, Luigi; Mans, Laura; Engelholm, Jean-Luc; Bali, Maria-Antonietta; Van Laethem, Jean-Luc; Eisendrath, Pierre (Endoscopy International Open, 2021)
Background and study aims In borderline resectable/locally advanced pancreatic ductal adenocarcinoma (PDAC), stereotactic body radiation therapy (SBRT) is an emerging neoadjuvant treatment option. Endoscopic ultrasound (EUS)-guided insertion of fiducial markers being a prerequisite, our aim was to assess its feasibility and safety and also to evaluate its success, from both the endoscopist’s and radiotherapist’s perspectives.Patients and methods We prospectively collected data concerning PDAC patients submitted to EUS-guided fiducial placement, from February 2018 to November 2019. Technical success was defined as at least one marker presumed inside the tumor. Quality success was assessed at pre-SBRT computed tomography, accordingly to the number of markers inside or < 1 cm from the tumor, number of markers at the tumor extremity, their location in different planes, the distance between them, and their distance from the biliary stent (if present). A new quality score was then proposed and high-quality success defined as at least six of 12 points.Results Thirty-seven patients were enrolled. A total of 97 fiducials were implanted, with a median of three fiducials per patient (0–4). The technical success rate was 92 %, with failure of fiducial placement in three patients. Three patients (8 %) had adverse events (fever, mild acute pancreatitis, and biliary stent migration). At pre-SBRT evaluation, two patients’ markers had migrated. The high-quality success rate was 62.5 %.Conclusions Our results contribute to demonstrating the feasibility and safety of EUS-guided fiducial placement for SBRT treatment in PDAC. It is hoped that the newly proposed quality score will pave the way for improving fiducial positioning and SBRT delivery.